2017
DOI: 10.1080/21580103.2017.1315963
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and validation of stem volume equations forPinus densiflora,Pinus koraiensis, andLarix kaempferiin South Korea

Abstract: Stem volume models using diameter at breast height (DBH) and height were developed for Pinus densiflora, Pinus koraiensis, and Larix kaempferi. The data were obtained from Gangwon, Gyeonggi, and North Gyeongsang provinces in South Korea, and the sample trees felled were used to provide the parameter estimates of volume equations. The combined-variable function, V ¼ a þ bD 2 H, was shown to be the best model through the validation of the equation. Also, the model using only DBH, V ¼ aD þ bD 2 was also evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Equation (model 2) has valid coefficients and good fit statistics for Dahurian larch species and is considered as the best model to predict the total volume. This result corresponded to previous studies, which concluded that Equation (model 2), the so-called combined-variable function, is the best fit model (Burkhart, 1977;Amateis and Burkhart, 1987;Sherrill et al, 2011;Lee et al, 2017).…”
Section: Estimation and Validation Of Volume Equationssupporting
confidence: 91%
“…Equation (model 2) has valid coefficients and good fit statistics for Dahurian larch species and is considered as the best model to predict the total volume. This result corresponded to previous studies, which concluded that Equation (model 2), the so-called combined-variable function, is the best fit model (Burkhart, 1977;Amateis and Burkhart, 1987;Sherrill et al, 2011;Lee et al, 2017).…”
Section: Estimation and Validation Of Volume Equationssupporting
confidence: 91%
“…Based on previously published papers, in forestry studies, many tree volume equations are used in different forms in order to develop tree volume equations (Saraçoğlu, 1988;Bi and Hamilton, 1998;Yavuz, 1999;Mısır and Mısır, 2004;Teshome 2005;Akindele and LeMay, 2006;Perez, 2008;Alegria and Tome, 2011;Hjelm and Johansson, 2012;Stolarikova et al, 2014;Malata et al, 2017;Lee et al, 2017;Özçelik and Çevlik 2017;Kitikidou et al, 2017;Sakıcı et al, 2018). In this study, following eighteen volume models in different forms obtained from the above-mentioned references are used.…”
Section: Methodsmentioning
confidence: 99%
“…Pinus densiflora (pine) are widely used as timber or fuel (Lee et al, 2017) and Quercus spp. (oak) are usually utilized as logs for mushroom cultivation (Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%